Arab Republic of Egypt : First Review Under the Extended Arrangement Under the Extended Fund Facility and Requests for Waivers for Nonobservance and Applicability of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Egypt's First Review Under the Extended Arrangement Under the Extended Fund Facility (EFF) and Requests for Waivers for Nonobservance and Applicability of Performance Criteria (PCs). All quantitative PCs for December 2016 were met, but a large depreciation of the pound is posing policy challenges. Because of higher costs of fuel products, the end-June targets for the fuel subsidy bill and the primary deficit are likely to have been missed. The authorities are taking corrective measures by implementing a stronger fiscal adjustment in the next two years, including through the fuel subsidy reform. The IMF staff supports the authorities' request for the completion of the first review under the Extended Arrangement under the EFF arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet